How to and why participate in the Technical Expert Review - CGIAR Initiative on Low-Emission Food Systems (2023)
The Technical Expert Review is a critical process in the implementation of the Paris Agreement. This webinar provided an overview of the review and discussed how we at Mitigate+ and our partners can take part in the review and why.